Editorial: Pedagogical policies and processes higher education in contemporaneity - Almeida, Maria de Lourdes Pinto de; Santos Filho, José Camilo dos (Universidade Estadual de Campinas, 2017)
It is with great satisfaction that we present this issue of RIESup that has as its thematic axis Policies and Processes of Higher Education in Latin America. Opening the debate is the article entitled Teaching in higher education: an analysis of the "three hundred" methodology and its relation with the historical-critical pedagogy, by Liliam Faria Porto Borges and Vanice Schossler Sbardelotto. The text presents a new analysis of teaching methodology called "Trezentos", which was developed by Professor Ricardo Ramos Fragelli of UnB since 2013. This methodology will work with the relationship between this methodology and progressive pedagogies, particularly the Historical-Critical Pedagogy, formulated and disseminated in Brazil by Dermeval Saviani. It is worth checking.